Em busca da liberdade : memória do movimento feminino pela anistia em Sergipe (1975-1979) - Oliveira, Maria Aline Matos de (2020)
This research analyzes the action of the Women's Movement for the Amnesty of Sergipe, founded in 1978. The civil-military dictatorship in Brazil was established in 1964, with a coup d'état. Persecution, torture, death, disappearance and exile were the arbitrary mechanisms used by the military to keep the dictatorial regime in power. The 1970s represented a milestone of crisis in the current system; In this sense, the opposition joined forces, and so the 1975 Women's Amnesty Movement, led by lawyer Therezinha Godoy Zerbine, set out to break rules and institute a National Campaign for Amnesty in favor of the redemocratization of the country. This campaign spans several Brazilian states. And in support of the National Movement, the nucleus of the Amnesty Women's Movement was founded in Sergipe, led by university professor Nubia Marques and a group of women, militants and relatives of political prisoners. This paper aims to investigate the Women's Committee for Sergipe Amnesty; To this end, it is intended to understand how the Movement was disseminated in the state, which campaigns, events and media were used in order to present the struggle of the MFPA to the society of Sergipe. Likewise, we intend to recover the memory of the MFPA and analyze the role of women as protagonist of history and instrument of political force, by founding the Women's Committee in the state. Regarding the research methodology, oral history is used, through interviews with members of the Women's Committee, as well as the analysis of Sergipe newspapers of the time and reports from the National Information Service. Finally, the research aims to contribute to the Brazilian historiographic production, highlighting the female protagonism in the amnesty campaign in Sergipe and Brazil.